KOMUNIKASI PENYULUHAN SATUAN BINAAN MASYARAKAT POLRES KARIMUN DALAM MENGANTISIPASI PEREDARAN NARKOBA PADA KALANGAN PELAJAR DI TANJUNG BALAI KARIMUN - Handayanti, Sri; Awza, Rusmadi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
A lot of information states that the negative impact caused by abuse in consuming drugs, this has not given a significant number in overcoming of drugs abuse. This is also the case in Tanjung Balai Karimun Regency, which is the legal area of the Polisi Resort Karimun which is part of a free trade area that is quite strategic because it is located on an international shipping lane. Causing the number of drugs cases in Tanjung Balai Karimun Regency is high. The number of cases in high school students is higher than that of elementary and junior high school students. This research aims to determine the communication planning and methods used in the communication of drugs counseling for the Community development unit Polisi Resort Karimun at the students level in Tanjung Balai Karimun in anticipating the circulation of drugs.This research uses qualitative research methods with the presentation of descriptive analysis, namely by describing the state of the subject or object of research based on the facts that appear. The informants in this research were 12 people taken based on purposive techniques. The data collection technique used is semi structured interview, participant observation and documentation of notes, data and photos of counseling that had been of activities carried out by the Polisi Resort Karimun relating to this research.. The interactive data analysis model the author uses to describe the results of the research in data analysis techniques and for checking the validity of the data the researcher uses the triangulation technique and the extension of participation.The results of the research showed that the communication planning of Polisi Resort Karimun Drugs counseling was an analysis of the problem by observation or observation directly which obtained data on the high number of drug cases in Tanjung Balai Karimun, especially among vocational high school students, So obtain data on the number of drugs user cases in Tanjung Balai Karimun and sought a solution to deal with the problem, namely by conducting counseling by Satbinmas Polres Karimun. Formulate clear communication goals, namely to reduce the number of drugs cases in the Tanjung Balai Karimun, especially among students by providing knowledge about the dangers of drugs. The selection of the right media is group media through face to face by gathering the audience, electronic media such as microphones, speakers, laptops, infocus, and audio-visual media and sometimes equipped with props form examples of drugs. In determining the approach used by defining an important audience to given counseling. Primary audiencaes that is students in adolescents with age criteria 14 years old and above in this case are junior and senior high school students, but are more focused on high school students because the number of cases is high. secondary audiences are additional targets with criteria of people living in Tanjung Balai Karimun. The method used is a group approach method that produces interaction and direct response from the audience so that communication is created in accordance with the expected goals of providing knowledge and changing attitudes.Keywords : Counseling Communication, Trafficking Of Drugs, Among Students.